Search Engine Optimization (SEO) As A Promotional Media On Google Search - Dedi Wijaya; Benny Daniawan; Yuki Gunawan (bit-Tech, 2021)
the current era, people's interest in using the internet is getting higher, this is because internet media has become an informative tool that can be accessed at any time. In searching for information, internet users usually use search engines. One of them is Google, the most widely used search engine. To find information in the Google search engine, we must use keywords. With SEO technique the website will be easy to find. A website optimization based on keywords, its implementation using On-page SEO and Off-page SEO mechanisms. On-page SEO is changing web pages according to the target keywords. By paying attention to important elements such as meta title, meta description, heading tags, text format, alt text, content, robot.txt, and sitemap.xml. Off-page SEO is a method that is carried out outside the website, creating relevant backlinks to the targeted website. This method can make the website as an organic promotional medium that brings traffic. In this research applying the concept of SEO both On-page and Off-page, the results obtained that there was a significant increase in traffic and based on the results of using the User Acceptance Test (UAT) with five aspects of component quality, this SEO support system can help in analyzing the website and as many as 82.3% of respondents said that the system built was very good